2021
DOI: 10.36740/wlek202107105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Durable Application of Protonic Pump Inhibitors on Cytokine Concentration in Rat Blood Serum

Abstract: The aim: Of the work was to determine the content of pro- and anti-inflammatory cytokines in the blood serum of the control group rats and after 28 days of inhibiting HCl secretion in the stomach by proton pump blockers “Omeprazole” and “Pantoprazole”. Materials and methods: The studies were performed on 30 white non-linear male rats weighing 160-180 g, divided into three groups with 10 animals in each. The control (group 1) were injected intraperitoneally with water for injections within 28 days once a day. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Thus, we observed a similar effect with angico gum. Results obtained for omeprazole, which is a potent proton pump inhibitor, were similar to those for angico gum in terms of wet weight and MPO activity due to the anti‐inflammatory effect of PPIs 29 …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, we observed a similar effect with angico gum. Results obtained for omeprazole, which is a potent proton pump inhibitor, were similar to those for angico gum in terms of wet weight and MPO activity due to the anti‐inflammatory effect of PPIs 29 …”
Section: Discussionsupporting
confidence: 58%
“…Results obtained for omeprazole, which is a potent proton pump inhibitor, were similar to those for angico gum in terms of wet weight and MPO activity due to the anti-inflammatory effect of PPIs. 29 Regarding mucosal integrity, angico gum prevented the loss of transepithelial electrical resistance and paracellular permeability, like omeprazole did. In this context, studies have demonstrated that cashew gum is also able to prevent the loss of mucosa in the larynx.…”
Section: Discussionmentioning
confidence: 96%